Immune-modulatory effect of human milk in reducing the risk of Kawasaki disease: A nationwide study in Korea - Jae Yoon Na; Yongil Cho; Yongil Cho; Juncheol Lee; Seung Yang; Seung Yang; Yong Joo Kim; Yong Joo Kim (Frontiers Media S.A., 2022)
BackgroundKawasaki disease (KD) is the most common acquired heart disease among children in developed countries, but the etiology is still unclear. There are several hypotheses regarding the outbreak of KD, including infection, genetics, and immunity. Since breastfeeding plays an essential role in the immune system's composition, investigating breastfeeding's effects on the occurrence of KD would be an excellent way to identify the etiology of KD.AimTo determine whether the incidence of KD decreases with breastfeeding.MethodsThis nationwide cohort study analyzed data from the National Health Insurance Service (NHIS) in South Korea and included 1,910,438 infants who underwent their first National Children's Health Examination (NCHE) between 2008 and 2014. Feeding types were collected using a questionnaire in NCHE. The NHIS data and NCHE data were merged and analyzed. First, we investigated the effect of breastfeeding on the development of KD at 1 year of age. Then, we surveyed the age at which no significant effect appeared by expanding the observation range yearly.ResultsThe most prevalent feeding type in the study population was exclusive breastfeeding (41.5%). At 10-12 months of follow-up age, 3,854 (0.2%) infants were diagnosed with KD. Compared to the exclusive formula feeding group, the adjusted odds ratio (aOR) for KD was 0.84 [95% confidence interval (CI), 0.78-0.90] and 0.86 (95% CI, 0.79-0.94) in the exclusive and partial breastfeeding groups, respectively. At 22-24 months of age, aOR for KD was 0.94 (95% CI, 0.90-0.98) in the exclusive breastfeeding group and 0.98 (95% CI, 0.92-1.03) in the partial breastfeeding group. There was no difference in the risk between the groups at 34-36 months.ConclusionsUsing a large amount of national data on children aged <2 years, we proved that breastfeeding has a protective effect on the development of KD.